Age‐ and CGG repeat‐related slowing of manual movement in fragile X carriers: A prodrome of fragile X‐associated tremor ataxia syndrome?. Issue 4 (1st February 2018) - Shickman, Ryan; Famula, Jessica; Tassone, Flora; Leehey, Maureen; Ferrer, Emilio; Rivera, Susan M.; Hessl, David
ABSTRACT: Background: Fragile X premutation carriers are at increased risk for fragile X‐associated tremor ataxia syndrome (FXTAS), but to date we know little about prediction of onset and rate of progression and even less about treatment of this neurodegenerative disease. Thus, the longitudinal study of carriers, and the identification of potential biomarkers and prodromal states, is essential. Here we present results of baseline assessments from an ongoing longitudinal project. Methods: The cohort consisted of 73 men, 48 with the fragile X mental retardation 1 ( FMR1 ) premutation (55‐200 cytosine‐cytosine‐guanine or CGG repeats) and 25 well‐matched controls (< 40 repeats) aged between 40 and 75 years. At enrollment, none met criteria for FXTAS or had any clinically significant tremor or ataxia by blinded neurological examination. The battery consisted of measures of visual memory, spatial working memory, response inhibition, motor speed and control, planning and problem solving, sustained attention, and a standardized movement disorder evaluation. Results: Contrary to expectations, there were no significant differences between premutation carriers and controls on any measure of executive function. However, the premutation carriers had significantly longer manual movement and reaction times than controls, and the significant interaction between CGG repeat and age revealed the slowest movement times among older carriers with higher CGG repeat alleles. A subset of premutation carriers had marginally lower scores on the ataxia evaluation, and they performed no differently from controls on the parkinsonism assessment. Conclusion: Early‐developing cerebellar or fronto‐motor tract white matter changes, previously documented in MRI studies, may underlie motor slowing that occurs before clinically observable neurological symptoms associated with FXTAS. © 2018 International Parkinson and Movement Disorder Society